Echo-location and evoked potentials of bats after ablation of inferior colliculus - Suga, N. (1969)
1. Echo-location and evoked potentials of blinded Yuma bats (Myotis yumanensis) were studied before and after ablation of the inferior colliculus (I.C.). A task of obstacle-avoidance was given to the bats: hits and misses of strands in the flight path were counted. Orientation sounds emitted by the bats during flight were recorded. 2. Bilateral ablation of the dorso-medial region of I.C. including the internuclear cortex and commissure had no effect on obstacle-avoidance performance. The bats avoided even strands of 0·2 mm diameter with orientation sounds. 3. Bilateral ablation of the dorsal half of I.C. including the external nucleus (lateral cortex) also had no effect on echo-location. 4. Bilateral ablation of the ventral half of I.C. caused severe deficiency in ability to avoid obstacles. The main nucleus appeared to be very important for echo-location. When bilateral ablation including the main nucleus was moderate, the bats failed to avoid strands of less than 0·5 mm diameter in spite of detecting them, but avoided large obstacles such as 3·7 mm strands. With severe bilateral ablation including the main nucleus, the bats did not avoid even the 3·7 mm strands in spite of frequent emission of orientation sounds, but often avoided crashing into the wall. 5. Severe unilateral ablation of I.C. including the main nucleus and a part of the lateral lemniscus had no effect on ability to avoid obstacles. Since sound localization by such bats are not explained by Van Bergeijk's model based on Békésy's, a modification of Van Bergeijk's model has to be considered. 6. Of the positive evoked potentials recorded with an active electrode placed at the dorsal surface of I.C., the slow component with a 7-9 msec peak latency reflected activity of inferior collicular neurones, while the fast component (N(4)) with a 3 msec peak latency represented activity of ascending lateral lemniscal fibres.